2020
DOI: 10.46377/dilemas.v35i1.2284
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico de los migrantes venezolanos atendidos en Rumichaca, 2018.

Abstract: El flujo migratorio hacia Ecuador aumentó a raíz de la crisis sociopolítica del país de Venezuela y con esto surgieron problemas de salubridad y seguridad. En la frontera norte ecuatoriana de Rumichaca se implementaron estrategias y acciones para apaciguar la emergencia; a raíz de esto, los objetivos buscaron establecer el perfil epidemiológico del migrante venezolano. La investigación encaminó una metodología cuali-cuantitativa; orientada a caracterizar el fenómeno, encaminar datos estadísticos, y res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Colombia self-reported prevalence of hypertension in 229 returning Colombians and Venezuelan migrants reached 12.5% (33). Local primary healthcare data analysis confirmed that essential hypertension was a common cause for seeking medical attention in some migrant communities in the region (34). Unique data from the Colombian Ministry of Health and Social Protection reported 9.938 Venezuelan migrants with hypertension out of 16.812 migrants registered with NCDs (35).…”
Section: Hypertension Among Migrants Residing In Latin Americamentioning
confidence: 94%
“…In Colombia self-reported prevalence of hypertension in 229 returning Colombians and Venezuelan migrants reached 12.5% (33). Local primary healthcare data analysis confirmed that essential hypertension was a common cause for seeking medical attention in some migrant communities in the region (34). Unique data from the Colombian Ministry of Health and Social Protection reported 9.938 Venezuelan migrants with hypertension out of 16.812 migrants registered with NCDs (35).…”
Section: Hypertension Among Migrants Residing In Latin Americamentioning
confidence: 94%